Factors Related to Knowledge, Attitudes and Behaviour with Scabies Incidence at Kuanfatu Health Center - Alunpah, Marchelino; Salmun, Johny A.R; Purnawan, Sigit (Timorese Journal of Public Health, 2022)
Scabies is a skin disease caused by Sarcoptes Scabiei Var hominis. In Indonesia, scabies is called kudis, gudik, or buduk, anyone who comes into contact with S. Scabiei can be infested with scabies. Scabies is a disease that is always included in the 10 most common diseases in the work area of ​​the Kuanfatu Health Center from 2018 to 2020. The purpose of this study was to analyze the relationship between the knowledge, attitudes, and behavior of people aged over 10 years with the incidence of scabies in the work area of ​​the Kuanfatu Health Center 2021. Research design uses analytical survey with the case-control method. The case population in this study were people aged over 10 years with the incidence of scabies and the control population was those who were not scabies. Case sampling was carried out by total sampling, while the control sample was taken using the purposive sampling method with the number of samples of cases and controls is 41people with ratio 1:1. The results obtained in this study stated that there was a significant association between knowledge (p = 0.008), bathing and changing behavior with the incidence of scabies (p = 0.006) and there was no significant association between attitudes with the incidence of scabies (p = 1.00). This study shows that there is an association between knowledge, bathing behavior, and changing people's clothes in the Kuanfatu Health Center with the incidence of scabies. Suggestions in this study are to provide understanding for the community through health promotion related to scabies disease so that people can understand and know the causes and ways to prevent scabies disease